Application of Talcott Parsons' Structural Functionalism Theory in Analyzing Social Systems and Modern Society Integration (International Journal of Economics Management and Social Science, 2026)
This article examines the application of Talcott Parsons' structural functionalism theory in analyzing contemporary social systems and modern society integration. Despite criticisms of its static nature and conservative assumptions, Parsonian functionalism remains relevant for understanding social stability, institutional interdependence, and integration mechanisms in complex modern societies. Drawing on recent developments in the World Social Report 2025 which highlights declining social trust, rising inequality, and social fragmentation, this study explores how Parsons' AGIL framework (Adaptation, Goal Attainment, Integration, and Latency) provides analytical tools for comprehending these challenges. Through systematic literature review and theoretical analysis, this research demonstrates that structural functionalism offers valuable insights into pattern maintenance, normative consensus, and system equilibrium despite profound societal transformations. The findings suggest that Parsonian concepts of social integration, value consensus, and functional prerequisites remain applicable when examining contemporary issues such as economic insecurity, institutional trust erosion, and social cohesion. This article contributes to ongoing debates about the continued relevance of classical sociological theory in understanding twenty-first century social dynamics. Keywords: Structural functionalism, Talcott Parsons, AGIL framework, social integration, modern society, social systems, value consensus, pattern maintenance